2022
DOI: 10.1002/jlb.4covcra0721-356rrr
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactive cellular, but not humoral, immunity is detected between OC43 and SARS-CoV-2 NPs in people not infected with SARS-CoV-2: Possible role of cTFH cells

Abstract: Multiple questions about SARS‐CoV‐2 humoral and cellular immunity remain unanswered. One key question is whether preexisting memory T or B cells, specific for related coronaviruses in SARS‐CoV‐2‐unexposed individuals, can recognize and suppress COVID‐19, but this issue remains unclear. Here, we demonstrate that antibody responses to SARS‐CoV‐2 antigens are restricted to serum samples from COVID‐19 convalescent individuals. In contrast, cross‐reactive T cell proliferation and IFN‐γ production responses were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Humoral immune responses from previous infections might also display cross-reactivity against SARS-CoV-2. SARS-CoV-2 cross-reacting antibodies have been detected in several [ 704 , 705 , 706 , 707 ], but not all [ 708 , 709 , 710 ] studies that analyzed sera obtained or intravenous immunoglobulin manufactured before the pandemic. Some studies found cross-reactive antibodies in only a small percentage of individuals [ 27 , 28 ], implying that genuine variability might have existed within or between populations, possibly related to differences in infection history.…”
Section: Host Factorsmentioning
confidence: 99%
“…Humoral immune responses from previous infections might also display cross-reactivity against SARS-CoV-2. SARS-CoV-2 cross-reacting antibodies have been detected in several [ 704 , 705 , 706 , 707 ], but not all [ 708 , 709 , 710 ] studies that analyzed sera obtained or intravenous immunoglobulin manufactured before the pandemic. Some studies found cross-reactive antibodies in only a small percentage of individuals [ 27 , 28 ], implying that genuine variability might have existed within or between populations, possibly related to differences in infection history.…”
Section: Host Factorsmentioning
confidence: 99%
“…In the peripheral blood, a subset of CD4 + T-cells with a similar phenotype and function has been described, termed circulating T FH cells (cT FH ) [21]. In COVID-19, cT FH have been proposed to play a crucial role in antiviral immunity [22]. SARS-CoV-2-specific cT FH are expanded in convalescent individuals, and are associated with antibody titers [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…At least, several types of cross-reactive CD8 + T cells and type 1 helper T cell (Th1) CD4 + T cells that support CTL functions [ 67 , 73 ] can influence disease severity and outcome [ 74 , 75 ]. The importance of cross-reactive, CD4 + follicular helper T (Tfh) cells that support antibody production remains to be determined [ 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%